Diagnosis Of Endothelial Dysfunction In Children With Neurocirculatory Dystonia: Test With Reactive Hyperemia - Umarova Mukaddas Abdukadirovna (Zien Journals, 2024)
The article examines the role of nitric oxide in the regulation of peripheral vascular tone in children with neurocirculatory dystonia. When using a functional test with reactive hyperemia, its high diagnostic significance was revealed; a decrease in the formation of nitric oxide in the vascular endothelium (endothelial dysfunction) was established in children with neurocirculatory dystonia (p <0.001).
Keywords: nitric oxide; neurocirculatory dystonia; endothelial dysfunction